iPSCs Derived from Malignant Tumor Cells: Potential Application for Cancer Research - Cheng, He; Liu, Chen; Cai, Xiaochen; Lu, Yu; Xu, Yongfeng; Yu, Xianjun (Current Stem Cell Research & Therapy, 2016)
The development of induced pluripotent stem cell (iPSC) technology has inspired a series of methods to manipulate cell fate and has provided novel insight into the profound molecular events underlying the development of diseases. Reprogramming somatic cells into iPSCs has been intensively investigated. However, few studies have investigated the reprogramming of malignant cells and its potential application. Herein, we review the recent progress of iPSCs derived from malignant cells, and highlight tumor iPSCs applications on cancer research which mainly focus on mesenchymal-epithelial transition, genetic and epigenetic change, diseases model construction, drug screening and tumor pathway study.
Keywords: Genetics and epigenetics